Understanding the context of design for social innovations: A methodological case study - Ortiz Nicolas, Juan Carlos (IGI Global, 2018)
The chapter describes the applicability of designers to the space of finding solutions to social issues through the generation of social innovations. Based on a literature review, it was evident that design requires new methods to apply to the resolution of social issues, and as such, this chapter presents a new method that supports designers in the development of solutions within the design for social innovation (DfSI) framework. The proposed method consists of six stages: (1) identifying the challenge, (2) analyzing the system in which the challenge co-exists, (3) understanding the system using user-centered design techniques, (4) defining the design brief, (5) generating proposals, and (6) evaluating and concluding. The chapter also introduces a design case study that describes in detail the implementation of the design method. The results indicated that the method supports designers to structure their process when aiming to design for social innovation and in particular to define the potential solution, which is reflected in a design brief.